The Regulation Prolems Of Individual Candidates And Single Candidates In The 2020 Elections - Widia Novita Lukitasari WA; Roby Cahyadi Kurniawan; Arizka Warganegara; Hertanto (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2022)
The simultaneous regional elections which will be held in December 2020 are marked by new democratic and political dynamics. The dynamics of the ITU are the birth of a single candidate in several regions that will carry out the regional elections. On the one hand, this shows that the dynamics of democracy on the ground are increasingly showing progress and our society is increasingly